OUTCOMES OF LAPAROSCOPIC VERSUS OPEN REPAIR OF DUODENAL ULCER PERFORATION (The Research of Medical Science Review, 2025)
Introduction: For the management of a perforated duodenal ulcer (PDUs), surgical intervention is the primary method. During this procedure, the perforation is sealed either with or without an omental patch. Open and laparoscopic repair are two commonly used approaches for repair of perforations. Aims and Objectives: To compare the outcomes of open repair with laparoscopic repair for perforated duodenal ulcers (PDUs). Place and Duration of Study: The study duration was March-2024 to September-2024 and was conducted in general surgery unit of Bahawal Victoria Hospital, Bahawalpur. Materials and Methods: This prospective study containing 104 patients having duodenal ulcer perforations were included. Patients of age 15-65 years who presented within 24 hours of symptoms onset were included. Group A (N=52) was the laparoscopic group while Group B (N=52) was the open repair group. Patients were kept under observation for 4 weeks, we recorded their operative time, hospital stay, post-operative complications such as intra-abdominal abscess formation, wound infection, leakage of repair requiring re-exploration. Results: Mean operative time was prolonged in group A; 93.4±37.1 minutes versus 78.1±43.5 minutes in group B (p-value 0.05). However, there was no significant difference in anastomotic leakage, wound infections rate and intraabdominal abscess between the groups. Wound infections occurred in 3 (5.8%) patients in group A and in 9 (17.3%) patients in group B (p-value 0.06). Mean hospital stay was significantly shorter in group A; 8.5±6.4 versus 12.1±9.8 days in group B (p- value 0.02). Conclusion: This study found that laparoscopic repair of PDUs was linked with longer operative times compared to open repair, but with shorter length of hospital stay and a decreased risk of infections. It is therefore possible to adopt laparoscopic surgery as a risk-free alternative to open repair in patients who have PDUs.